CFD-Based Analysis of Wingsail Shape and Placement on a Fishing Vessel in Southern Bali Waters - Sukmawardana, Happy Nabila; Suwarni, Endah; Purnamasari, Dian; Utina, Mohammad Ridwan; Rina, Rina; Setiyobudi, Nanang; Sulistyawati, Wiwin (Department of Naval Architecture - Diponegoro University, 2026)
The maritime transportation sector contributes significantly to atmospheric emissions due to its reliance on fossil fuels, underscoring the need for more energy-efficient, environmentally friendly propulsion technologies. One promising solution is Wind-Assisted Ship Propulsion (WASP), which uses wind energy as a supplemental power source for vessel propulsion. Among various WASP technologies, wingsails have attracted attention for their rigid airfoil geometry and their ability to generate aerodynamic lift efficiently. This study aims to investigate the influence of wing sail shape and placement on aerodynamic performance, to identify an effective configuration for vessel applications. Computational Fluid Dynamics (CFD) simulations are conducted using k- SST turbulence model. Two symmetric airfoil profiles, NACA 0012 and NACA 0015, are examined under angle of attack variations of 5°, 0°, 5°, 10°, 15°, and 20°. The wingsail is modeled in two installation configurations: midship and a combined midship-aft arrangement. Simulations are performed at wind speeds of 4 m/s, 10 m/s, 13.7 m/s, and 17.2 m/s, with aerodynamic performance evaluated based on the lift and drag coefficients. Based on the results, the NACA 0015 wingsail shows more stable aerodynamic behavior than the NACA 0012, while medium wind speeds in the range of 10–13.7 m/s offer the best balance between lift and drag. In addition, the midship–aft wingsail arrangement consistently generates higher lift than the single midship configuration, making the NACA 0015 wingsail with midship–aft placement the most suitable choice for fishing vessel applications.